Recent advances in the diagnostic and therapeutic roles of microRNAs in colorectal cancer progression and metastasis - Liang, Chen; Yang, Jing-Bo; Lin, Xin-Yi; Xie, Bi-Lan; Xu, Yun-Xian; Lin, Shu; Xu, Tian-Wen (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is the third most common malignancy in the world and one of the leading causes of cancer death; its incidence is still increasing in most countries. The early diagnostic accuracy of CRC is low, and the metastasis rate is high, resulting in a low survival rate of advanced patients. MicroRNAs (miRNAs) are a small class of noncoding RNAs that can inhibit mRNA translation and trigger mRNA degradation, and can affect a variety of cellular and molecular targets. Numerous studies have shown that miRNAs are related to tumour progression, immune system activity, anticancer drug resistance, and the tumour microenvironment. Dysregulation of miRNAs occurs in a variety of malignancies, including CRC. In this review, we summarize the recent research progress of miRNAs, their roles in tumour progression and metastasis, and their clinical value as potential biomarkers or therapeutic targets for CRC. Furthermore, we combined the roles of miRNAs in tumorigenesis and development with the therapeutic strategies of CRC patients, which will provide new ideas for the diagnosis and treatment of CRC.